Morphological and Anatomical Variations of Vicia faba L. Seedlings in Response to Static Magnetic Force - Taia, Wafaa K.; Bassiouni, Eman M.; Eltelet, Safaa A. (Scientific Journal of University of Benghazi, 2021)
Static magnetic force (SMF) is the most important factors affecting all living creatures. This force investigated for its effect on human physiology, animal behavior and migration and plant germination and horticulture. Vicia faba seeds subjected to static magnetic forces arising from iron magnetic (4.0X2.5X1.0 cm, Y30H) in two regimes. The first one (A) post soaked seeds exposed to five magnetic cycles for 30 minutes and 30 minutes in between the two cycles. Then these seeds (A) soaked in tap water for six hours before starting the germination. The second portion (B), first soaked in tap water (Presoaked) for six hours, then exposed to the five cycles beside the Blank seeds. Germination %, seedlings morphology and anatomical structure recorded throughout the experiment which last for about 26 days. The germination % increased in the first regime (A) than the control, while the second regime (B) delayed the germination till the first two weeks and then respond to be as the blank ones. The most effective seedlings portions are the root system, the leaf color and area, leaf ptyxis , number of cortex layers, chlorophyll density beside the type of vascular bundles as well as xylem/phloem ratio. SMF has great effect on seed germination, seedling morphology andanatomicalstructure of the stem.